USABILITY TESTING DENGAN USE QUESTIONNAIRE PADA APLIKASI ABSENSI PEGAWAI SIM REMBANGKAB - Panthera Dikanuzqi Ramadhani Soepriyadi (2022)
Information technology is developing rapidly today. In the digital era, there are useful and creative information services, for example websites. The website can provide information on an official office in the form of a summary contained on the website. The website is useful for sharing information within the official office. Sim Rembangkab website is an official office website used by Dintanpan Rembang employees as a medium for recaping employee attendance data, the website contains various important information for users. Dintanpan Rembang is an office that works in the field of agriculture and food for the community, which aims to develop the quality of agricultural and food products for the community and as an extension service office for the local community in managing agriculture and food products. The method used in this research is usability testing. Data collection was carried out by distributing questionnaires containing questions prepared for Dintanpan employees. The measurement aims to determine the results of usability, convenience, satisfaction, and evaluation of the usability of the Dintanpan Sim Rembangkab website. Usability on the rembangkab web sim determines how easy it is for users to use an application that is used.